Optimizing Fresh-Cut Apple (Malus sylvestris (L.) Mill.) Quality Through Combination of Sodium Alginate and Calcium Chloride Coatings - Maharani Retna Duhita; Muhammad Khairul Ikhsan (University of Sultan Ageng Tirtayasa, 2024)
Fresh-cut fruit is a fruit product innovation that makes it easier for people to consume fruit, but it is not shelf-stable, which results in a decline in the physicochemical and organoleptic quality of the fruit. For example, cut apples are prone to browning and rotting, reducing their shelf life and quality. Fruit can be preserved in a variety of methods, one of which is by covering it with a solution of calcium chloride (CaCl) and sodium alginate (SA). This study aimed to assess the impact of different SA and CaCl combination coating concentrations on the physicochemical properties of fresh-cut apples (Malus sylvestris (L.) Mill.). This study is a descriptive experimental with 3 replications with 4 treatments, namely P1: 1% SA+1% CaCl, P2: 2% SA+2% CaCl, P3: 3% SA+3% CaCl, and control (no coating). The study was conducted at the Biochemistry and Food Laboratory of the Biology Study Program of UIN Maulana Malik Ibrahim Malang and the Animal Husbandry Laboratory of Universitas Brawijaya. Parameters observed included physicochemical characteristics (firmness, weight loss, color, moisture content, total soluble solids, titrated acidity). Data were analyzed by ANOVA followed by Duncan's test at 95% confidence level. From the results of the study, it is known that P2 is the best combination coating. We concluded that a coating of 2% sodium alginate and 2% calcium chloride on cut apples led to improved quality, including reduced weight loss, better color, and higher moisture content, compared to other coating combinations